Acute exercise in a hot environment increases heat shock protein 70 and peroxisome proliferator-activated receptor γ coactivator 1α mRNA in Thoroughbred horse skeletal muscle - Ebisuda, Yusaku; Mukai, Kazutaka; Takahashi, Yuji; Yoshida, Toshinobu; Kawano, Aoto; Matsuhashi, Tsubasa; Miyata, Hirofumi; Kuwahara, Masayoshi; Ohmura, Hajime (Frontiers in Veterinary Science, 2023)
Heat acclimatization or acclimation training in horses is practiced to reduce physiological strain and improve exercise performance in the heat, which can involve metabolic improvement in skeletal muscle. However, there is limited information concerning the acute signaling responses of equine skeletal muscle after exercise in a hot environment. The purpose of this study was to investigate the hypothesis that exercise in hot conditions induces greater changes in heat shock proteins and mitochondrial-related signaling in equine skeletal muscle compared with exercise in cool conditions. Fifteen trained Thoroughbred horses [4.6 ± 0.4 (mean ± SE) years old; 503 ± 14 kg] were assigned to perform a treadmill exercise test in cool conditions [COOL; Wet Bulb Globe Temperature (WBGT), 12.5°C; n = 8] or hot conditions (HOT; WBGT, 29.5°C; n = 7) consisting of walking at 1.7 m/s for 1 min, trotting at 4 m/s for 5 min, and cantering at 7 m/s for 2 min and at 90% of VO2max for 2 min, followed by walking at 1.7 m/s for 20 min. Heart rate during exercise and plasma lactate concentration immediately after exercise were measured. Biopsy samples were obtained from the middle gluteal muscle before and at 4 hours after exercise, and relative quantitative analysis of mRNA expression using real-time RT-PCR was performed. Data were analyzed with using mixed models. There were no significant differences between the two groups in peak heart rate (COOL, 213 ± 3 bpm; HOT, 214 ± 4 bpm; P = 0.782) and plasma lactate concentration (COOL, 13.1 2 This is a provisional file, not the final typeset article